DAMPAK KEBIJAKAN PEREKONOMIAN ERA ORDE BARU - Rafan Fadhlurrahman; Salman Badawi (Journal of Current Research In Multidisciplinary, 2023)
Various scholars and linguists have examined pragmatics as a concept. The fundamental problem associated with description, definition or explanation in terms of acceptance is that there is no universality (Levinson, 2009). Pragmatics as a concept is not a distinction. Addressing some insights about what is meant by pragmatics and what it reflects is a view of its scope. Gadzar (1979, p. 2) is of the view that "pragmatics has the topic of aspects of the meaning of utterances which cannot be explained by direct reference to the truth conditions of the uttered sentences."